Ta có: \(\left(\frac{1}{1\cdot3}+\frac{1}{3\cdot5}+\frac{1}{5\cdot7}+...+\frac{1}{13\cdot15}\right)\cdot\left(x-1\right)=\frac{3}{5}x-\frac{7}{15}\)
\(\Leftrightarrow\left(\frac{1}{1}-\frac{1}{3}+\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+...+\frac{1}{13}-\frac{1}{15}\right)\cdot\left(x-1\right)=\frac{3x}{5}-\frac{7}{15}\)
\(\Leftrightarrow\frac{14}{15}\cdot\left(x-1\right)=\frac{9x-7}{15}\)
\(\Leftrightarrow x-1=\frac{9x-7}{15}:\frac{14}{15}=\frac{9x-7}{14}\)
hay \(x=\frac{9x-7}{14}+1=\frac{9x-7}{14}+\frac{14}{14}=\frac{9x+7}{14}\)
\(\Leftrightarrow x\cdot14=9x+7\)
\(\Leftrightarrow14x-9x-7=0\)
\(\Leftrightarrow5x-7=0\)
\(\Leftrightarrow5x=7\)
hay \(x=\frac{7}{5}\)
Vậy: \(x=\frac{7}{5}\)